Pendidikan Islam Dalam Krisis Manusia Modern: (Perspektif Filsafat Perennial) - Sutikno, Sutikno (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2017)
This study focuses the Perenialism philosophy perspective of Islamic education in the crisis of modernity of wave of contemporary capitalism and liberalism. Crisis of modern man was rised since early periode of enlightenment caused by domination and ideologization of positivisim, rationalism and empirism those rised capitalism dan liberalism was forced by globalization machine that penetrates to whole of world territory. Those domination and ideologization centered to instrumental rationality based on ideological process to all aspects of human life. Islamic education in the crisis of modernity was qualitative research which used library research methods. Analise of this This study was philosophical and ideological approaches. Conclusion of this study that perenial perspective was an alternative solution in the crisis of modernity . Philosophically, perenial perspective was used as critical paradigm to deconstruct and reconstruct instrumental rationality in the modern paradigm capitalistically and liberalistically. In Islamic education, perenial perspective was a foundation of curricula construction through sociological and philosophical dialectics both in socio cultural structures or educational institutions.